INCREASE OF FIRMNESS OF FETTLING OF DSP-2 AT USING THE BURNED MAGNESIA CALCIC FLUX IN CONDITIONS OF JSC «BMZ» – MANAGEMENT COMPANY OF HOLDING «BMK» - I. A. Bondarenko; A. K. Turygin; A. L. Artamoshin; A. V. Feklistov; A. V. Vengura (Литьë и металлургия)
It is shown that the burned magnesia calcic flux of JSC “Complex “Magnesite” production is recommended for industrial use on all steel-smelting units of JSC “BMZ —management company BMK holding” on the basis of positive results on increase in firmness of fettling DSP-2.